Children's Understandings of Well-being : Towards a Child Standpoint - Fattore, Tobia; Mason, Jan; Watson, Elizabeth (Children's Well-Being: Indicators and Research,, 2017)
The book presented here describes an outstanding attempt, not only to include children's views but to partner with children to develop the concept of well-being and to study the phenomenon as the children understand it. The authors do this by placing the concept of children's well-being within the existing discourses on the topic and by developing their unique theoretical approach to the concept. Then, and based on what children told them, the authors identify different domains and dimensions of children's well-being and touch upon its multifaceted nature. The book concludes with drawing research and policy implications from an integrated summary of the study's findings and lists indicator concepts that present an alternative framework and conceptualisation of well-being from a child standpoint. .